Control Design of the Wave Compensation System Based on the Genetic PID Algorithm - Mingjian Zhou; Yuqin Wang; Haibing Wu (Advances in Materials Science and Engineering)
The transfer function of the wave compensation system is deduced. The interference signal acting on the system is eliminated by the feed-forward compensation correction method. The pole assignment of the system is carried out after eliminating the interference signal. The genetic PID algorithm is proposed, and the genetic PID controller is designed. The control block diagram of the wave compensation system based on the genetic PID control algorithm is established, and the optimal index and PID parameters are optimized by the crossover and mutation operators of the genetic particle swarm optimization algorithm. The simulations and experiments of the system show that the control performance of the wave compensation system based on the genetic PID algorithm is greatly improved. The higher control precision is obtained. The anti-interference ability and the robustness of the system are increased. The accuracy of the control method is verified.